Steady boundary layer slip flow along with heat and mass transfer over a flat porous plate embedded in a porous medium. - Aziz, A.; Siddique, J.I.; Aziz, T. (Public Library of Science, 2014)
In this paper, a simplified model of an incompressible fluid flow along with heat and mass transfer past a porous flat plate embedded in a Darcy type porous medium is investigated. The velocity, thermal and mass slip conditions are utilized that has not been discussed in the literature before. The similarity transformations are used to transform the governing partial differential equations (PDEs) into a nonlinear ordinary differential equations (ODEs). The resulting system of ODEs is then reduced to a system of first order differential equations which was solved numerically by using Matlab bvp4c code. The effects of permeability, suction/ injection parameter, velocity parameter and slip parameter on the structure of velocity, temperature and mass transfer rates are examined with the aid of several graphs. Moreover, observations based on Schmidt number and Soret number are also presented. The result shows, the increase in permeability of the porous medium increase the velocity and decrease the temperature profile. This happens due to a decrease in drag of the fluid flow. In the case of heat transfer, the increase in permeability and slip parameter causes an increase in heat transfer. However for the case of increase in thermal slip parameter there is a decrease in heat transfer. An increase in the mass slip parameter causes a decrease in the concentration field. The suction and injection parameter has similar effect on concentration profile as for the case of velocity profile.
Keywords: Article; concentration (parameters); fluid flow; geometry; heat transfer; mass transfer; mathematical analysis; mathematical model; physical parameters; physical phenomena; temperature; velocity; slip flows; porous materials; plates; incompressible flow; Ordinary differential equations; Plate work manufacturing